Poly(l-glutamic acid)-cisplatin nanoformulations with detachable PEGylation for prolonged circulation half-life and enhanced cell internalization - Jiang, Zhongyu; Feng, Xiangru; Zou, Haoyang; Xu, Weiguo; Zhuang, Xiuli (Bioactive materials, 2021)
PEGylation has been widely applied to prolong the circulation times of nanomedicines via the steric shielding effect, which consequently improves the intratumoral accumulation. However, cell uptake of PEGylated nanoformulations is always blocked by the steric repulsion of PEG, which limits their therapeutic effect. To this end, we designed and prepared two kinds of poly(l-glutamic acid)-cisplatin (PLG-CDDP) nanoformulations with detachable PEG, which is responsive to specific tumor tissue microenvironments for prolonged circulation time and enhanced cell internalization. The extracellular pH (pHe)-responsive cleavage 2-propionic-3-methylmaleic anhydride (CDM)-derived amide bond and matrix metalloproteinases-2/9 (MMP-2/9)-sensitive degradable peptide PLGLAG were utilized to link PLG and PEG, yielding pHe-responsive PEG-pHe-PLG and MMP-sensitive PEG-MMP-PLG. The corresponding smart nanoformulations PEG-pHe-PLG-Pt and PEG-MMP-PLG-Pt were then prepared by the complexation of polypeptides and cisplatin (CDDP). The circulation half-lives of PEG-pHe-PLG-Pt and PEG-MMP-PLG-Pt were about 4.6 and 4.2 times higher than that of the control PLG-Pt, respectively. Upon reaching tumor tissue, PEG on the surface of nanomedicines was detached as triggered by pHe or MMP, which increased intratumoral CDDP retention, enhanced cell uptake, and improved antitumor efficacy toward a fatal high-grade serous ovarian cancer (HGSOC) mouse model, indicating the promising prospects for clinical application of detachable PEGylated nanoformulations. [Display omitted] •The poly(l-glutamic acid)-cisplatin nanoformulations with detachable PEGylation are developed for cancer therapy.•DePEGylation of nanoformulations triggered by tumor microenvironment exhibit enhanced tumor cell internalization.•The dePEGylation strategy exhibits promising prospects for clinical application of nanomedicines.